Redefining assessment for sustainability: a reflective approach to curriculum transformation in environmental education - David, James Ojochenemi (Frontiers in Education, 2025)
BackgroundThe urgency of sustainability challenges has reinforced the need for effective environmental education in higher education. However, certain assessment methods often fail to balance theoretical depth with individual accountability. The shift toward digital and hybrid learning post-COVID-19 further necessitates adaptive, student-centered assessment models.ObjectivesThis study critically evaluates assessment practices within the Environmental Sustainability (EVST) module at a University of Technology in South Africa. It identifies key limitations in project-based assessments and proposes a revised framework integrating diverse formative and summative strategies to enhance engagement and real-world application.MethodsUsing Schön’s reflective practitioner model, the study draws on teaching experiences, collegial discussions, and professional development insights. It critiques past assessment methods and introduces an alternative approach based on formative and summative assessment theories, constructive alignment, and student-centered learning. The revised model incorporates technology-driven quizzes, individual essays, and structured group projects to provide a more balanced evaluation that takes cognizance of modern digital realities.ResultsThe findings indicate that technology-driven quizzes enhance digital literacy and real-time feedback, individual essays improve research and analytical skills, and structured group projects foster collaboration while ensuring equitable participation. The revised model aligns with the university’s graduate attributes by promoting problem-solving, self-directed learning, and environmental responsibility.ConclusionThis study underscores the need for continuous assessment refinement in environmental education, particularly in digital learning environments. By integrating adaptive assessment methods, educators can bridge the gap between theoretical knowledge and practical sustainability action, fostering critical thinking and engagement. The proposed framework offers a model for curriculum transformation and future research on assessment strategies